Combined association of insufficient physical activity and sleep problems with healthcare costs: a longitudinal study - Kikuti-Koyama, Kelly Akemi; Lemes, Ítalo Ribeiro; Morais, Luana Carolina de; Monteiro, Henrique Luiz; Turi-Lynch, Bruna Camilo; Fernandes, Rômulo Araújo; Codogno, Jamile Sanches (São Paulo Medical Journal, 2025)
BACKGROUND: The magnitude of economic losses attributed to sleep problems and insufficient physical activity (PA) remains unclear. This study aimed to investigate the association between insufficient PA, sleep problems, and direct healthcare costs. OBJECTIVE: To investigate the association between insufficient physical activity (PA), sleep problems, and direct healthcare costs among adults. DESIGN AND SETTING: Adults aged ≥ 50 years attended by the Brazilian National Health Service were tracked from 2010 to 2014. METHODS: Direct healthcare costs were assessed using medical records and expressed in US. Insufficient PA and sleep problems were assessed through face-to-face interviews. Differences were identified using the analysis of covariance and variance for repeated measures. RESULTS: In total, 454 women and 166 men were enrolled. Sleep problems were reported by 28.9% (95%CI: 25.2% to 32.4%) of the sample, while insufficient PA was reported by 84.8% (95%CI: 82.1% to 87.6%). The combination of sleep problems and insufficient PA explained 2.3% of all healthcare costs spent on these patients from 2010 to 2014, which directly accounts for approximately US 4,765.01. CONCLUSION: The combination of sleep problems and insufficient PA plays an important role in increasing direct healthcare costs in adults. Public health stakeholders, policymakers, and health professionals can use these results to reinforce the need for strategies to improve sleep quality and increase PA, especially in nations that finance their National Health Systems.